2023
DOI: 10.1002/ejhf.2848
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic peptides: role in the diagnosis and management of heart failure: a scientific statement from the Heart Failure Association of the European Society of Cardiology, Heart Failure Society of America and Japanese Heart Failure Society

Abstract: Natriuretic peptides, brain (B-type) natriuretic peptide (BNP) and N-terminal prohormone of brain natriuretic peptide (NT-proBNP) are globally and most often used for the diagnosis of heart failure (HF). In addition, they can have an important complementary role in the risk stratification of its prognosis. Since the development of angiotensin receptor-neprilysin inhibitors (ARNIs), the use of natriuretic peptides as therapeutic agents has grown in importance. The present document is the result of the Trilatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 134 publications
(293 reference statements)
1
17
0
Order By: Relevance
“…Hence, the increased serum levels of FGF21 and the decreased expression of KLB following MI may reflect a compensatory response to FGF21 resistance ( 5 ). Similarly, cardiac remodeling or HF is accompanied by the elevated expression of natriuretic peptides, suggesting that the intravenous injection of natriuretic peptides could also provide additional benefits to improve HF symptoms ( 33 ). The findings of the present study and those of other studies suggest that the targeted restoration of cardiac KLB expression significantly promotes the activation of FGF21 receptor-dependent pathways in rats post-MI, closely associated with improvements in cardiometabolic parameters, suggesting an increase in FGF21 sensitivity ( 5 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the increased serum levels of FGF21 and the decreased expression of KLB following MI may reflect a compensatory response to FGF21 resistance ( 5 ). Similarly, cardiac remodeling or HF is accompanied by the elevated expression of natriuretic peptides, suggesting that the intravenous injection of natriuretic peptides could also provide additional benefits to improve HF symptoms ( 33 ). The findings of the present study and those of other studies suggest that the targeted restoration of cardiac KLB expression significantly promotes the activation of FGF21 receptor-dependent pathways in rats post-MI, closely associated with improvements in cardiometabolic parameters, suggesting an increase in FGF21 sensitivity ( 5 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…The role of natriuretic peptides to establish the diagnosis of HF is established in international HF guidelines 10–12 . A scientific statement by three HF Societies (Heart Failure Association of the European Society of Cardiology, Heart Failure Society of America and Japanese Heart Failure Society) provides a comprehensive and updated perspective for the use of natriuretic peptides in the prognostic stratification, management and treatment of HF 13 …”
Section: Natriuretic Peptidesmentioning
confidence: 99%
“…It has recently been observed that left ventricular ejection fraction (LVEF) may have a U‐shaped relationship with mortality with an increase in the risk of death also in patients with a LVEF >65% 15,16 . These patients with supranormal (sn) LVEF (HFsnEF) may have peculiar characteristics compared to those with preserved ejection fraction (HFpEF), with a higher risk of events and a lower response to medical treatment, namely neurohormonal antagonists 16–20 . A recent study included 621 patients with HFpEF, of whom 302 had HFsnEF.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Building on these promising outcomes, we subsequently conducted a single-arm, open-label, multicenter study to assess the e cacy of tranilast as an additional therapy for patients with MD and heart failure, with BNP levels > 100 pg/mL during standard cardiac protection therapy [12]. BNP is a standard cardiac function indicator that is highly correlated with the severity and prognosis of heart failure [13,14]. In MD, a BNP level ≥ 100 pg/mL is considered a predictive risk factor for death [15].…”
Section: Introductionmentioning
confidence: 99%